Sistem Penyiraman Otomatis Pada Tanaman Hias Dengan Menggunakan Blynk dan NodeMCU - Rizky Nur Prasetyo; R. Tommy Gumelar; Elliya Sestri (Jurnal Teknologi Informasi (JUTECH), 2022)
The development of Internet of Things (IoT) technology has had a major impact on various aspects of life, including agriculture and plant care. This research aims to design a solution that can overcome the challenges of irrigating ornamental plants by utilizing soil moisture sensors and IoT technology. The approach used in this study is Hardware Programming. This approach involves leveraging hardware and programming to design and implement an IoT-based automatic watering system for ornamental plants. In its implementation, the NodeMCU ESP8266 acts as the control center, while the soil moisture sensor is used to measure soil moisture levels, the DHT11 sensor is used to measure ambient temperature, and the ultrasonic sensor is used to measure the volume of water in the container. The data obtained from these sensors is integrated with the Blynk application. The test results show that the system is able to provide an accurate and fast response regarding soil moisture conditions, as well as making it easier for users to monitor watering through mobile devices. This research contributes to overcoming plant care challenges by utilizing IoT technology and integration with the Blynk platform. It is hoped that this solution will provide benefits, especially for Tangerang Express Park rangers, so that they can monitor plant conditions in real-time.